Essential tobacco dependence medicines in 137 countries. (29th October 2020) - Benipal, Simran; Budhram, Dalton R.; Bilimoria, Krish; Woods, Hannah; Wang, Ri; Persaud, Nav
Abstract: Aims: To use a database of national essential medicine lists to determine how many include the three tobacco dependence medicines: nicotine replacement therapy, varenicline and bupropion. Methods: Retrospective observational study using national essential medicine lists for 137 countries. Results: Of the 137 countries, 34 listed at least one of the three tobacco dependence medicines included in this analysis. Bupropion was listed by 23 countries, nicotine replacement therapy by 17 countries and varenicline by eight countries. Conclusions: Tobacco dependence medicines do not appear on the essential medicines lists of most countries.